“Ink Me”: A Representation of Transparency in Election Administration - Li, Lean; Mohd Don, Zuraidah (2010)
The Malaysian Election Commission has to present itself as fair, transparent and competent in its preparations for elections. Malaysia recently went through its twelfth general election, and while the Election Commission was busy with its preparations, it also had to be seen to be neutral in its treatment to all Malaysians, including the contesting parties. This paper shows how the Election Commission was represented by the media in the days following the announcement of the general election. Besides that, the analysis is also focussed on the strategies used by the Election Commission to present themselves more credibly and transparent to all the relevant parties and voters concerned. The study uses the technique of critical discourse analysis to analyse a corpus of articles taken from The Star from 13 February to 7 March 2008.